The Past Tense Forms in “Prosta Mova”: On Materials of the Peresopnytsia Gospels in Comparison with the 1580’s V. Tjapinski’s Gospel - Смирнова, Екатерина Андреевна Андреевна (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]The present article deals with the evolution of the past tense forms in ‘prosta mova’, basing on The Peresopnytsia Gospels (further on PG). The study traces the formation, variation and the Polish linguistic influence on ‘prosta mova’ past tense. Special attention is paid to the problem of translation and the uneven distribution of the past tense forms in PG in comparison with the 1580’s V. Tjapisnki Gospel. The comparative analysis and the description of two verbal systems of the past tense are shown in the table.
Keywords: “prosta mova”, perfect, pluperfect, V. Tjapinski’s Gospel, The Peresopnytsia Gospels